Efterfrågan av grova sågade dimensioner och hyvlade produkter bland Wallnäs AB:s kunder - Selmeryd, Oskar (2005)
The purpose of this thesis is to study whether there is a demand for sawn wood products of large dimensions and planed goods among Wallnäs AB:s customers. The thesis consist of two main parts, one survey among Wallnäs present customers and another one which purpose is to increase Wallnäs customer base. Finally there is a chapter that describes what properties the raw material has to have in order to produce the demanded products.